When students write Tape 2 - Ralph Fletcher Joann Potalupi (Stray light media)
Although writing encompasses a bundle of skills, it could be roughly divided into two main branches -composing (craft) and editing (mechanics). In this tape, we explore how skilled writing teachers teach mechanics such as contraction and spelliing. At Bailey`s the techers demostrate how important skills are taugth in the context of an ongoing writing workshop.
Area-Documental
Keywords: Genero-Guías educativas